Procedural justice and perceived electoral integrity: the case of Korea's 2012 presidential election. Issue 7 (9th November 2016) - Cho, Youngho; Kim, Yong Cheol
ABSTRACT: Recently, there has been an increase in the number of scholars focusing on why voters around the world differ in their evaluations of electoral integrity. One group of scholars contends that perceived electoral integrity is determined by partisan status according to election results. Another group claims that individual perception of election quality is influenced by such political cues as institutional support for election management bodies. Although the two groups have developed this subject differently, they both underestimate the degree to which the election process affects electoral integrity. Based on the theory of procedural justice, this study argues that the more problems citizens see in the electoral process, the more negatively they tend to rate elections. An analysis of a public opinion survey conducted immediately after the December 2012 presidential election in South Korea provides credible evidence for our theoretical expectations and presents an important implication for elections of new democracies in a comparative perspective.